2014
DOI: 10.2478/sjph-2014-0022
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Smoking and Socio-Demographic Characteristics in Correlation with Low Birth Weight: A Turin (Piedmont) Study

Abstract: Key words: low birth weight, maternal smoking, newborn, pregnancy, risk factorsIntroduction. 15 to 25% of women smoke during pregnancy. Scientific evidence suggests that exposure to smoking causes decreased birth weight. The aim of this study was to assess the correlation between smoking during pregnancy, maternal sociodemographic characteristics, and low birth weight.Methods. Data were derived from 1572 questionnaires administered to each woman that gave birth at the Gynecology Teaching Hospital "S. Anna" in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
(15 reference statements)
2
4
0
Order By: Relevance
“…We found that with every one-week increase in gestational age, the odds of LBW significantly decreased. As observed in previous studies, pre-term babies are usually underweight, therefore, once delivery occurs at term the likelihood of a baby weighing above 2.5 kg is high [10]. Our findings further suggest that the odds of LBW significantly increase with increasing parity, which is in line with the findings of several authors [9, 15, 27].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found that with every one-week increase in gestational age, the odds of LBW significantly decreased. As observed in previous studies, pre-term babies are usually underweight, therefore, once delivery occurs at term the likelihood of a baby weighing above 2.5 kg is high [10]. Our findings further suggest that the odds of LBW significantly increase with increasing parity, which is in line with the findings of several authors [9, 15, 27].…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, after adjusting for the residence of mothers, secondary or higher education remained a significant predictor of birth weight and mothers who attained this level of education were 63% less likely to have LBW infants. This finding is congruent with several studies which link LBW to the educational level of mothers [10, 31, 39]. A possible explanation for this might be that increased years of maternal education brings about improvement in ANC attendance, nutritional status, health-seeking behaviour and enhanced maternal experiences relative to pregnancy and childcare.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A higher prevalence of smoking during pregnancy in adolescents is congruent with other studies ( 28 ). Smoking has been recognised as an important risk factors for having SGA newborns ( 29 ) and has also been linked to a higher incidence of low birth weight newborns ( 30 ). We observed a much higher incidence in nuchal translucency in women aged 20–24 years than in adolescents.…”
Section: Discussionmentioning
confidence: 99%